From a Disposable Ureteroscope to an Active Lightweight Fetoscope—Characterization and Usability Evaluation - Legrand, Julie (IEEE Robot Autom Lett, 2018)
The twin-to-twin transfusion syndrome is a severe fetal anomaly appearing in up to 15% of identical twin pregnancies. This anomaly occurs when twins share blood vessels from a common placenta. The complication leads to an unbalanced blood transfusion between both fetuses. A current surgical treatment consists in coagulating the shared vessels using a fetoscope with an embedded laser. Such treatment is very delicate and constraining due to limited vision and size of the insertion area. The rigidity and lack of controllability of the current used instruments add an additional difficulty and limit the choice in insertion site. This letter proposes an improved flexible fetoscope, offering an enhanced laser controllability and higher versatility regarding the location of the insertion site. A better approach angle can therefore be realized. Also, tissue damage may be further reduced. This single-handed controllable active fetoscope is obtained after adaptation of a LithoVue (Boston Scientific, Natick, MA, USA), a commercially available passive flexible ureteroscope. The LithoVue is fitted with a unique lightweight add-on actuation module foreseen of an artificial muscle and a dedicated control system. Experiments in a mixed reality trainer suggested that the proposed fetoscope is compact, ergonomic, and intuitive in use, allowing an adequate control of the flexible end.